Model Pembelajaran Latihan Konjungsi Bahasa Jerman Menggunakan Satzkarten: Model Pembelajaran Latihan Konjungsi Bahasa Jerman Menggunakan Satzkarten - Fauzan Adhima (Universitas Negeri Surabaya, 2022)
This study aims to develop the stages of learning German conjunction grammar exercises using the Satzkarten game. The method used in this research is qualitative with literature study techniques. The Satzkarten game is a German sentence card game that is combined using the right conjunction.The conjunctions chosen in the learning model using the Satzkarten game are aber, oder, denn, deshalb, und on the theme